Systematic Literature Review : Tren Penerapan Elemen Gamifikasi dalam Platform E- Commerce - Filda Dwi Meirina; Arista Pratama; Siti Mukaromah (MDP Student Conference, 2026)
The implementation of gamification elements on e-commerce platforms has continued to expand, however comprehensive mapping of dominant elements, implementation trends, and user impacts remains limited. Therefore, this study aims to identify the most frequently used gamification elements, analyze implementation trends, and examine their impacts on e-commerce users. This study employs a Systematic Literature Review of empirical articles published between 2021 and 2026, retrieved from Scopus, ScienceDirect, SpringerLink, Emerald Insight, and Google Scholar, resulting in 25 selected articles. The synthesis results indicate that points/coins and rewards are the most dominant elements, supported by leaderboards and challenges, while immersive elements remain relatively underutilized. Furthermore, customer engagement emerges as the most frequently examined outcome, while customer loyalty and repurchase intention are also reported as important outcomes in previous studies. These findings suggest that current e-commerce gamification primarily focuses on enhancing user engagement rather than developing sustainable user experiences.